DEVELOPMENT OF A DESIGN SCHEME OF A SINGLE-SUPPORT DRIVE SYSTEM WITH AEROSTATIC BEARINGS - Breshev, Oleksii; Bashta, Oleksandr; Nosko, Pavlo; Bashta, Alla; Spivak, Oleksandr; Semak, Inna (Problems of Friction and Wear, 2025)
This study introduces an enhanced computational model for a single-support spindle system equipped with aerostatic bearings, intended for use in semi-automatic monocrystal cutting machines. The model addresses critical geometric and operational features specifically, a low relative bearing length (λ < 0.5) and conical support surfaces which are not adequately considered in conventional calculation methodologies. To improve modeling accuracy, the original bearing geometry is transformed into an equivalent radial configuration, allowing adaptation of an existing method. The approach includes the assessment of radial displacements and evaluates the influence of gas-lubricant parameters, supply pressure, and stiffness coefficients. The proposed model enables more precise estimation of the bearing’s load-carrying capacity and stiffness, thereby enhancing the operational stability and performance of the spindle unit. The findings emphasize the importance of accounting for specific geometric deviations in bearing analysis.